Fostering Team Creativity Through Team-Focused Inclusion: The Role of Leader Harvesting the Benefits of Diversity and Cultivating Value-In-Diversity Beliefs. Issue 4 (August 2022) - Leroy, Hannes; Buengeler, Claudia; Veestraeten, Marlies; Shemla, Meir; Hoever, Inga J.
This article advances prior theory on inclusive leadership to better understand how leaders foster team creativity through members' experience that their uniqueness belongs within the team (i.e., team-derived inclusion). We argue that leaders can instigate such sense of inclusion in their team by engaging in two behaviors: stimulating all members of the team to fully express their unique viewpoints and perspectives ( harvesting the benefits of diversity ) and facilitating beliefs about the value of differences in the team ( cultivating value-in-diversity beliefs ). In Study 1 ( n = 491 employees), we validated newly developed scales measuring these two leader behaviors. Using a sample of 38 teams within one organization (Study 2), we showed that harvesting the benefits of diversity, without also cultivating value-in-diversity beliefs, has a negative effect on team-derived inclusion and indirectly team creativity. In Study 3, we demonstrated based on 93 teams from multiple organizations, while ruling out several alternative explanations, that harvesting the benefits of diversity positively relates to team-derived inclusion and indirectly team creativity, if leaders also cultivated value-in-diversity beliefs . Our model and findings across studies are the first to shed light on inclusive leadership as double-edged sword in that leaders may need to complement harvesting with cultivating to prevent negative effects and elicit positive effects on inclusion and, eventually, team creativity.